2018
DOI: 10.1111/ctr.13380
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in preemptive referral for kidney transplantation in Georgia

Abstract: Background Racial disparities persist in access to kidney transplantation. Racial differences in preemptive referral, or referral prior to dialysis start, may explain this discrepancy. Methods Patient-level data on kidney transplant referrals (2005–2012) from all Georgia transplant centers were linked to the United States Renal Data System to examine racial disparities in preemptive referral, waitlisting, and living donor transplant. Adjusted logistic regression and Cox proportional hazard models determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 42 publications
1
59
0
Order By: Relevance
“…In general, the current study results confirmed that many of the associations that have been identified as barriers to initial kidney transplantation persist for evaluating access to repeat transplantation. Race and ethnicity were associated with preemptive listing for repeat transplantation, as has been demonstrated in prior studies evaluating access to primary transplantation . These results persisted with adjustment for demographic and clinical factors as well as indicators for socioeconomic status and social factors based on insurance type, educational attainment, and residential distress index.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In general, the current study results confirmed that many of the associations that have been identified as barriers to initial kidney transplantation persist for evaluating access to repeat transplantation. Race and ethnicity were associated with preemptive listing for repeat transplantation, as has been demonstrated in prior studies evaluating access to primary transplantation . These results persisted with adjustment for demographic and clinical factors as well as indicators for socioeconomic status and social factors based on insurance type, educational attainment, and residential distress index.…”
Section: Discussionsupporting
confidence: 70%
“…Race and ethnicity were associated with preemptive listing for repeat transplantation, as has been demonstrated in prior studies evaluating access to primary transplantation. 9,22,23 These results persisted with adjustment for demographic and clinical factors as well as indicators for socioeconomic status and social factors based on insurance type, educational attainment, and residential distress index. The degree to which these differences are based on timely referral and identification of failing graft function and are amenable to interventions targeting access to care among ESRD patients is important to evaluate.…”
Section: Discussionmentioning
confidence: 84%
“…We extended this work to two distinct stages of the kidney transplant process and among a population who have overcome referral-related Table 3. Testing of mediation of SES, comorbidity, or SES and comorbidity on listing for kidney transplant within 1 year between black versus white patients with kidney failure (n53013) or receipt of transplant between black versus white kidney transplant candidates on the waitlist (n52068), using inverse odds ratio weighting and among a population who have started the transplant evaluation process disparities (4,(6)(7)(8)(9). It is at this point that transplant centers engage with candidates and have opportunities to influence the coordination of the transplant process (18,30).…”
Section: Discussionmentioning
confidence: 99%
“…These results should be considered in light of important limitations. Our cohort is a select group of candidates who have overcome significant barriers to be referred to and seen at transplant clinic (8,9). A majority of black candidates were recruited at one site and our sample size is modest (n53013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation